2010
DOI: 10.1002/chem.200902487
|View full text |Cite
|
Sign up to set email alerts
|

SN2’ versus SN2 Reactivity: Control of Regioselectivity in Conversions of Baylis–Hillman Adducts

Abstract: TiCl(4)-induced Baylis-Hillman reactions of alpha,beta-unsaturated carbonyl compounds with aldehydes yield the (Z)-2-(chloromethyl)vinyl carbonyl compounds 5, which react with 1,4-diazabicyclo[2.2.2]octane (DABCO), quinuclidine, and pyridines to give the allylammonium ions 6. Their combination with less than one equivalent of the potassium salts of stabilized carbanions (e.g. malonate) yields methylene derivatives 8 under kinetically controlled conditions (S(N)2' reactions). When more than one equivalent of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 86 publications
1
26
0
Order By: Relevance
“…, the E parameters of the thiophene series 1a–d cover a domain of electrophilic reactivity of 4 orders magnitude from the weakest electrophile 1d ( E = −21.33) to the strongest ones 1a ( E = −17.18). Figure also reveals that the thiophenes 1a–d used in this study display an electrophilicity that compares well with that of 4‐(2,2‐bis‐(phenylsulphonyl)vinyl)‐ N , N ‐dimethylaniline 9 ( E = −16.53) , the substituted pyridinium salt 10 ( E = −17.90) , the 3‐methoxybenzaldehyde 11 ( E = −19.32) , and the diethyl 4‐methyl‐benzylidenemalonate 12 ( E = −21.11) , respectively, but lower than that of 1,3,5‐trinitrobenzene 8 ( E = −13.19) , the conventional aromatic electrophile in S N Ar processes and the 3,5‐difluoro‐substituted benzhydrylium ion 5 ( E = 8.02), the most electrophilic species known to date . Within the E scale developed by Mayr and co‐workers, the electrophilicity of the most reactive thiophene, i.e., 1a ( E = −17.18) appears to be higher than that of some benzylidenemalonate such as the substituted diethyl benzylidenemalonate 4 ( E = −23.80), but have an E value lower by 11 units than that of 7‐chloro‐4,6‐dinitrobenzofuroxan 6 and 7‐chloro‐4,6‐dinitrobenzofurazan 7 ( E = −6.11) .…”
Section: Methodssupporting
confidence: 60%
See 1 more Smart Citation
“…, the E parameters of the thiophene series 1a–d cover a domain of electrophilic reactivity of 4 orders magnitude from the weakest electrophile 1d ( E = −21.33) to the strongest ones 1a ( E = −17.18). Figure also reveals that the thiophenes 1a–d used in this study display an electrophilicity that compares well with that of 4‐(2,2‐bis‐(phenylsulphonyl)vinyl)‐ N , N ‐dimethylaniline 9 ( E = −16.53) , the substituted pyridinium salt 10 ( E = −17.90) , the 3‐methoxybenzaldehyde 11 ( E = −19.32) , and the diethyl 4‐methyl‐benzylidenemalonate 12 ( E = −21.11) , respectively, but lower than that of 1,3,5‐trinitrobenzene 8 ( E = −13.19) , the conventional aromatic electrophile in S N Ar processes and the 3,5‐difluoro‐substituted benzhydrylium ion 5 ( E = 8.02), the most electrophilic species known to date . Within the E scale developed by Mayr and co‐workers, the electrophilicity of the most reactive thiophene, i.e., 1a ( E = −17.18) appears to be higher than that of some benzylidenemalonate such as the substituted diethyl benzylidenemalonate 4 ( E = −23.80), but have an E value lower by 11 units than that of 7‐chloro‐4,6‐dinitrobenzofuroxan 6 and 7‐chloro‐4,6‐dinitrobenzofurazan 7 ( E = −6.11) .…”
Section: Methodssupporting
confidence: 60%
“…The E values are listed and compared in Fig. with those obtained in previous studies by Terrier and co‐workers for 7‐chloro‐4,6‐dinitrobenzofuroxan 6 , 7‐chloro‐4,6‐dinitrobenzofurazan 7 , and 1,3,5‐trinitrobenzene 8 , together with substrates 4 , 5 , and 9–12 previously investigated by Mayr and co‐workers .…”
Section: Methodsmentioning
confidence: 95%
“…This versatile class of compounds is readily available from the Morita–Baylis–Hillman reaction, an organocatalyzed coupling of aldehydes with α,β‐unsaturated esters, ketones or nitriles that represent a 100 %‐atom‐economy process. Besides the overwhelming amount of research on the Morita–Baylis–Hillman reaction, which can be inferred from the number of recent reviews and reports published in this creative area of research,8 only a few papers have been dedicated to defining the mechanistic aspects of nucleophilic substitution reactions involving the allylic backbone characteristic of the Morita–Baylis–Hillman adducts 912…”
Section: Introductionmentioning
confidence: 99%
“…Upon exposure of MBH acetates to a substoichiometric amount of triphenylphosphane (20 mol‐%) in the presence of 2‐trimethylsilyloxyfuran (TMSOF), regiospecific allylic substitution occurs to provide γ‐butenolides in good to excellent yields, with high region‐ and diastereoselectivities. Krische suggested that the phosphane‐catalyzed allylic substitution of MBH acetates exhibited an exceptionally high level of regiospecificity through a tandem S N 2′/S N 2' mechanism (Scheme ) 9,11. The generation of an electrophile–nucleophile ion pair, which suppresses direct addition of the nucleophile to the less substituted enone moiety of the starting MBH acetate, is proposed as a key step in this catalytic transformation.…”
Section: Introductionmentioning
confidence: 99%